In-silico, Synthesis, Characterization, and In-vitro Studies on Benzylidene-based 2-chloroquinolin Derivatives as Free Radical Scavengers in Parkinson’s Disease - Subramanian, Gomathy; Prasad, Kaveri; Chand, Jagdish; Amarjith, Thiyyar K.; Shanish, Antony A. (Drug Research, 2024)
Parkinson’s disease is the loss of dopaminergic neurons in the substantial nigra part of the brain leading to neurodegeneration. Whereas, reactive oxygen species and mitochondrial impairment are considered to be the major pathophysiology of neurodegeneration. The benzylidene-based 2-chloroquinolin derivatives were synthesized and characterized by FT-IR, NMR, and MS spectrometry which were screened using various in-silico approaches. The designed compounds were further assessed using in-vitro cytotoxicity assay by the MTT method, DPPH assay, and Glutathione measurements in the SHSY5Y neuroblastoma cell lines. The compounds JD-7 and JD-4 were found to have a binding affinity of − 7.941 and − 7.633 kcal/mol with an MMGBSA score of − 64.614 and − 62.817 kcal/mol. The compound JD-7 showed the highest % Cell viability of 87.64% at a minimal dose of 125 µg/mL by the MTT method. The neurotoxicity effects were observed at increasing concentrations from 0 to 125, 250, and 500 µg/mL. Further, free radical scavenging activity for the JD-7 was found to be 36.55 at lowest 125 µg/mL concentrations. At 125 µg/mL, GSH % and GSSG % were found to be increasing in rotenone treatment, whereas JD-7 and JD-4 were found in the downregulation of glutathione level in the pre-treated rotenone SHSY5Y neuroblastoma cell lines. The benzylidene-based chloroquinolin derivatives were synthesized, and among the compounds JD-1 to JD-13, the compounds JD-7, and JD-4 were found to have having highest % cell viability, free radical scavenging molecules, and glutathione levels in the SHSY5Y neuroblastoma cell lines and could be used as free radical scavengers in Parkinson’s disease.
Keywords: in-silico studies; reactive oxygen species; SHSY5Y neuroblastoma cell lines; in-vitro studies; neurodegeneration; Parkinson’s disease